Preliminary Phytochemical Screening and Assessment of Pharmacological Activities of Leaves and Stems of Gynura procumbens (Lour.) Merr. - Akhi, Tuz Mia Nur; Adib, Mohiminul; Islam, Quazi Sufia; Sultana, Irin; Haider, Rafiqul; Ibrahim, Muhammad (Bangladesh Pharmaceutical Journal, 2019)
The present study was designed to evaluate the preliminary phytochemical profiles and pharmmacological activities of different extractives (methanol and chloroform) of the leaves and stems of Gynura procumbens (Lour.) Merr. Preliminary phytochemical screenings demonstrated the presence of alkaloids, glycosides, steroids, flavonoids, tannins, saponins, gums and amides and reducing sugar in leaves and stems. Significant α-amylase inhibitory activities were found by the methanol (66.67%) and chloroform (70.63%) extracts of leaves of G. procumbens as compared to the standard drug acarbose (95.45%) at a concentration of 400 μg/ml. In the castor oil-induced diarrhea, the maximum inhibition of defecation was found by the chloroform fraction. During the anxiolytic activity test which was performed by open field and hole cross method, different extractives of leaves and stems of G. procumbens (500 mg/kg bw) reduced the total count of square crossed and hole crossed to a considerable extent in comparison to the control groups. In antipyretic assay, both extracts reduced the temperature to a significant extent in comparison to the standard group. Bangladesh Pharmaceutical Journal 22(1): 79-84, 2019